An Analytical Study of Bodhisattva Concept in Mahāyāna Buddhism - Hoi, Ven. Vo Van (The Journal of International Association of Buddhist Universities (JIABU), 2018)
It’s not difficult to discern that the ideal of Bodhisattva can be derived from the Arahant’s ideal. Concerning the development of the Mahāyāna Bodhisattva doctrine, the most accessible documentation for this is found in the original Buddhist sutras. The early concept of Bodhisattva was related only to the Buddha as found in the Buddhist scriptures such as Dīgha Nikāya, Majjhima Nikāya, etc. Later Mahāyāna Buddhism developed the Bodhisattva theory in the important Mahāyāna sutras. The difference between Mahāyāna and Theravāda Buddhism is the number of Bodhisattvas that appeared in the two systems of the sutras. But the Bodhisattva in Mahāyāna Buddhism is the personification of the characteristics of the Buddha such as compassion, loving-kindness, and wisdom. Considering the historical context and geographical spread of Buddhism, the author believes that this change was suitable to propagate the Dharma.